Post‐hematopoietic stem cell transplantation relapse: Role of checkpoint inhibitors. Issue 2 (8th March 2022) - Roshandel, Elham; Tavakoli, Farzaneh; Parkhideh, Sayeh; Akhlaghi, Sedigheh Sadat; Ardakani, Maria Tavakoli; Soleimani, Masoud
Abstract: Background and Aims: Despite the revolutionary effects of hematopoietic stem cell transplantation (HSCT) in treating hematological malignancies, post‐HSCT relapse is considered a critical concern of clinicians. Residual malignant cells employ many mechanisms to evade immune surveillance and survive to cause relapse after transplantation. One of the immune‐frustrating mechanisms through which malignant cells can compromise the antitumor effects is misusing the self‐limiting system of immune response by overexpressing inhibitory molecules to interact with the immune cells, leading them to so‐called "exhausted" and ineffective. Introduction of these molecules, known as immune checkpoints, and blocking them was a prodigious step to decrease the relapses. Methods: Using keywords nivolumab, pembrolizumab, and ipilimumab, we investigated the literature to figure out the role of the immune checkpoints in the HSCT setting. Studies in which these agents were administrated for relapse after transplantation were reviewed. Factors such as the interval from the transplant to relapse, previous treatment history, adverse events, and the patients' outcome were extracted. Results: Here we provided a mini‐review discussing the experiences of three immune checkpoints, including nivolumab, pembrolizumab, and ipilimumab, as well as the pros and cons of using their blockers in relapse control after HSCT. In conclusion, it seems that CI therapy seems effective for this population. Future investigations may provide detailed outlook of this curative options.